Influence of Discharge and ?h?nn?l G??m?try on S????g? Losses from S???nd?ry ??n?l - Shаikh Nооr Mustаfа; Mаngriо Munir Аhmеd; Tаlрur Mаshооquе Аli; Issаni Mushtаq Аhmеd (PSM Biological Research, 2018)
S????g? is th? m?st serious f?rms ?f w?t?r loss in ?n irrig?ti?n ??n?l n?tw?rk. S????g? l?ss m?stly d???nd ?n th? ?h?nn?l g??m?try. ?x??ssiv? s????g? l?ss?s ??n ??us? w?t?r l?gging ?nd s?il s?linity du? t? whi?h th? ?ultiv?bl? ?r? r?du??d, ?nd r?sults in ? l?ss ?f ??t?nti?l ?r?? ?r?du?ti?n. In this ????r, s????g? l?ss fr?m ? (S?rki Min?r) th?t ?ff t?k?s fr?m Sh?hu br?n?h ?f J?m?r?? ??n?l w?s d?t?rmin?d. R?l?v?nt hydr?uli? d?t? w?s r???rd?d ?t str?t?gi? l???ti?ns ?nd s????g? l?ss?s w?r? m??sur?d by infl?w- ?utfl?w m?th?d r?s???tiv?ly. Lin??r r?gr?ssi?n w?s ?m?l?y?d t? d?v?l??? ?m?iri??l r?l?ti?ns f?r ??m?uting s????g? l?ss?s with r?s???t t? ?h?nn?l g??m?try. ??-Ty?? ?nd ?ygmy ?urr?nt m?t?rs w?s us?d t? m??sur? th? dis?h?rg? ?t th? diff?r?nt s??ti?n. Th? r???rd?d d?t? ?f hydr?uli? ?h?r??t?risti?s w?s ??rr?l?t?d using lin??r r?gr?ssi?n ?n?lysis t? d?v?l?? ?n ?m?iri??l ?qu?ti?n f?r s????g? l?ss?s with ?h?nn?l g??m?try ??r?m?t?rs.Th? results r?v??l?d th?t th? m?ximum s????g? l?ss?s w?r? ?t 0-5RD (4%) f?ll?w?d by 5-10RD (3.4%), 10-15RD (3.4%) 15-20RD (3.5%), ?nd th?n 20-25RD (2.9%) ?nd ?v?r ?ll s????g? l?ss?s w?s 17% in th? min?r. Statistical analysis (LRA) shows significantly positive relationship at (?<0.05) f?r s????g? l?ss?s and dis?h?rg? (r2=0.962), w?tt?d ??rim?t?rs (r2=0.943), fl?w ?r?? (r2=0.914) ?nd t?? width (r2=0.967). Th?s? ?qu?ti?ns ??uld b? us?d t? ?stim?t? ??n?l s????g? l?ss?s with?ut g?ing thr?ugh th? ??nv?nti?n?l m?th?d.